2015
DOI: 10.1371/journal.pone.0125836
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment with Vitamin D/MOG Association Suppresses Experimental Autoimmune Encephalomyelitis

Abstract: Experimental autoimmune encephalomyelitis (EAE) is an animal model to study multiple sclerosis (MS). Considering the tolerogenic effects of active vitamin D, we evaluated the therapeutic effect of myelin oligodendrocyte glycoprotein (MOG) associated with active vitamin D in EAE development. EAE was induced in female C57BL/6 mice by immunization with MOG emulsified with Complete Freund’s Adjuvant plus Mycobacterium tuberculosis. Animals also received two intraperitoneal doses of Bordetella pertussis toxin. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 41 publications
2
43
2
Order By: Relevance
“…MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptide (YRSPFSRVVHLYRNGK, Immunostep, Salamanca, Spain), >95% pure, was chosen because it is a target epitope in MS patients [18]. Liposomes were composed of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (sodium salt) (DOPS, Lipoid, Steinhausen, Switzerland) and 1,2-didodecanoyl-snglycero-3-phosphocholine (DLPC, Lipoid), and cholesterol (CH, Sigma Aldrich, MO, USA).…”
Section: Liposomes and Peptidesmentioning
confidence: 99%
See 3 more Smart Citations
“…MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptide (YRSPFSRVVHLYRNGK, Immunostep, Salamanca, Spain), >95% pure, was chosen because it is a target epitope in MS patients [18]. Liposomes were composed of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (sodium salt) (DOPS, Lipoid, Steinhausen, Switzerland) and 1,2-didodecanoyl-snglycero-3-phosphocholine (DLPC, Lipoid), and cholesterol (CH, Sigma Aldrich, MO, USA).…”
Section: Liposomes and Peptidesmentioning
confidence: 99%
“…Lipids were dissolved in chloroform and the solvent was removed by evaporation under vacuum and nitrogen. The lipids were hydrated with the appropriate buffer (phosphate-buffered saline [PBS], 0.5 mg/ml solution of MOG [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] peptide) and the liposomes obtained were homogenized to 1 μm by means of an extruder (Lipex Biomembranes, Vancouver, Canada). Encapsulation efficiencies (EE) were calculated according to the equation EE (%) = [(C peptide, total -C peptide, out )/C peptide, total ] × 100, where C peptide, total is the initial MOG 40-55 peptide concentration and C peptide, out is the concentration of nonencapsulated peptide.…”
Section: Liposomes and Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…Confirming this hypothesis, we recently demonstrated that a combined therapy with MOG + VitD blocked EAE development. This elevated efficacy was correlated with reduced production of IL-6 and IL-17 by spleen and CNS cell cultures stimulated with MOG, reduced splenic DC maturation, and also a striking decline in CNS inflammation [119] (Figure 2). Figure 2.…”
Section: Therapeutic Effect Of Vitd In Eaementioning
confidence: 92%